Hasan Basri Agus' Contribution to Islamic Education Policy: An Anxiology study on the Development of Quality Human Resources in Jambi - Rizky Firnanda; Irfan Maulana Adnan; Muhammad Ridwan Faqih; Naseh Ulwan (Yayasan Al Hidayah, 2026)
This study aims to analyze the contribution of Hasan Basri Agus (HBA) in the formulation and implementation of Islamic religious education policy in Jambi province, with an axiological approach that emphasizes the formation of character and development of Human Resources (HR) quality. HBA's background as a bureaucrat and pesantren alumni provides its own color in the public policies that he promulgated, especially by combining religious values and nationalism in regional development strategies. This study uses descriptive qualitative methods with data collection techniques through in-depth interviews, participatory observation, and documentation of policy archives and other supporting documents. The results showed that the policy of Islamic religious education during the leadership of HBA focused on three main things: strengthening access and quality of madrasah and pesantren, granting scholarships abroad for teachers and students, as well as the construction of Islamic education support facilities such as student dormitories and learning facilities in the villages. Axiological values such as justice, equality, scholarship, and spirituality form the basis of the policy. The real impact of this policy is reflected in the increase in Jambi's Human Development Index (HDI) and the emergence of a diaspora of Muslim intellectuals from Jambi who are active at the national and international levels. This study concluded that the value-based approach undertaken by HBA in the field of Islamic religious education is not only relevant, but also effective in forming superior human resources and character. These findings make an important contribution to the discourse of Islamic education policy in Indonesia, as well as offering transformative policy models that can be applied in different regions with similar socio-religious contexts